2020
DOI: 10.3389/fpsyg.2020.589281
|View full text |Cite
|
Sign up to set email alerts
|

The Distance Between the “Self” and the “Other” in Children’s Digital Books

Abstract: This conceptual paper contributes toward our understanding of the underlying mechanisms in children's understanding of self and the other with media. We synthesize diverse bodies of literature, concerned with children's reading with digital and traditional (print) books, to explicate the parameters that may, in part, explain positive learning outcomes and further illuminate the patterns across various measures. We propose the "Distance Model," which suggests that a child's interest in a reading activity depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…(2) Consider supporting children's self-expression through adult intervention Children's sharing can evolve as a social means of further engagement with the story, providing a self-directed entry point to the narrative content [8,24]. It has been shown that parental reading companionship can enhance children's reading ability, which is conducive to developing children's interest in reading and early reading awareness [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…(2) Consider supporting children's self-expression through adult intervention Children's sharing can evolve as a social means of further engagement with the story, providing a self-directed entry point to the narrative content [8,24]. It has been shown that parental reading companionship can enhance children's reading ability, which is conducive to developing children's interest in reading and early reading awareness [25,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Adding story-based elements to all early childhood MBIs might be a result of the fact that listening to stories is a daily activity for kindergarten and preschool aged children. The lack of story-based elements in middle childhood programs was somewhat surprising, considering the fact that characters from stories can be models for children of all ages, and stories can provide a psychological distance that can be especially useful when exploring negative emotions, behaviors or thoughts experienced in everyday life (Ahmed, Somerville & Sebastian, 2018;Kucirkova & Littleton, 2020;Orvell, Kross & Gelman, 2019). Importantly, there is evidence that even preschoolers prefer realistic stories over fantasies (Barnes, Bernstein & Bloom, 2015) as processing fantasy can overwhelm neural resources required for daily life, like the executive functions (Lillard et al, 2015), which are crucial considerations for future interventions with story-based elements.…”
Section: Discussionmentioning
confidence: 99%
“…Adding story-based elements to all early childhood MBIs might be because listening to stories is a daily activity for kindergarten and preschool children. The lack of story-based elements in middle childhood programs were somewhat surprising, considering the fact that characters from stories can be models for older children as well, and stories can provide a psychological distance that can be especially useful when exploring negative emotions, behaviors or thoughts experienced by the self in everyday life (Ahmed et al, 2018;Kucirkova & Littleton, 2020;Orvell et al, 2019). Importantly, it has been found that even preschoolers prefer realistic stories over fantasies (Barnes, Bernstein & Bloom, 2015) as processing fantasy can overwhelm neural resources required for daily life, like the executive functions (Lillard et al, 2015), which are crucial considerations for future interventions with story-based elements.…”
Section: Discussionmentioning
confidence: 99%